Exercise Habits and Family Disease History as Determinant of Activity Intolerance and ECG Patterns of Patients with Acute Coronary Syndrome (ACS) - Wiwiek Retti Andriani; Agus Wiwit Suwanto; Heru Wiratmoko; Agung Eko Hartanto; Sumy Dwi Antono; Endang Purwaningsih; Gandes Widya Hendrawati; Mirza Failasufi; Langgeng Cahyono (Health Notions, 2022)
Acute Coronary Syndrome (ACS) occurs due to blockage of coronary blood vessels which causes a decrease in oxygen flow and advanced conditions has an impact on physical activity. Factors associated with activity intolerance and ECG patterns suc as: sex, age, education, history of previous illnesses, exercise habits, family history of illness. The study involved all patients diagnosed with NSTEMI in the ICCU room at RSUD Dr. Harjono, a sample of 30 respondents was selected using a consecutive sampling technique. This research was analyzed by multivariate analysis.  The result of this research showed that factors that influence the tolerance of the activities of patients with coronary heart disease were sports habits and a history of previous illnesses. The respondent's habit of exercising affected the complaints that arise during the activity (each p-value was less tha 0.05). As conclusion, factors that affect the activity intolerance of coronary heart disease patients are physical exercise habits and family history of disease. Keywords: determinant factors; activity intolerance; ECG patterns; acute coronary syndrome